Implementation of an AI Agent Chatbot with a Dynamic Knowledge Base from Google Drive for Journal Information Service - Huzain Azis; Randika sakha Ramadani Putra Ahmad; Irawati Syahriawan (yocto brain, 2026)
This study presents the implementation of an AI agent chatbot to support journal information services on the Open Journal Systems (OJS) platform and the Telegram messaging application using a dynamic knowledge base sourced from Google Drive. The chatbot provides automated responses to user inquiries related to journal scope, publication fees, submission procedures, and review timelines, while allowing journal administrators to update information content without modifying the system. Functional testing results indicate that the chatbot delivers accurate and consistent information with acceptable response times across both platforms. The implementation demonstrates that integrating an AI agent chatbot with a dynamic knowledge base can enhance information accessibility, reduce administrative workload, and improve service efficiency in academic journal management